PENGARUH SENAM BUGAR LANSIA INDONESIA TERHADAP KESEIMBANGAN DINAMIS PADA WANITA USIA 60-79 TAHUN 2015 (Journal of Sport Coaching and Physical Education, 2017)
Elderly experienced many setbacks physical condition as a result of the aging process. The problem in this research is there any effect of Senam Bugar Lansia Indonesiato dynamic balance in women aged 60-79 in 2015? The purpose of the research is analyzing the effect of Senam Bugar Lansia Indonesia to dynamic balance in woman aged 60-79 in 2015. The purpose of the research is analyzing the effect of Senam Bugar Lansia Indonesia to dynamic balance in woman aged 60-79 in 2015.